Estratégias de ensino para acadêmicos surdos na educação superior - Lima, Juliana Corrêa de (2018)
This study aims to understand how the teaching strategies used by the teachers contribute to the learning of deaf students in the Graduation Courses of the Federal University of Santa Maria (UFSM). The research was anchored in the qualitative approach with systematization from the Content Analysis by thematic categories and in the speeches of the subjects surveyed from the interview and questionnaire, the use of these data collection techniques made it possible to analyze the issues of inclusion, accessibility and the different strategies that help deaf academics ensure their learning in the courses they attend. It was perceived the need for changes in the way of teaching and that the teaching strategies used by the teachers do not contribute to deaf students to follow the content, as well as the lack of actions beyond the classroom that also include attitudinal changes, of relationships and communication between listeners and deaf people. In conclusion, new questions were set, which confers the importance and continuity to the studies in this subject. Besides that, the learning focus of deaf students seems to lie only on teaching strategies associated with cognitive abilities and not with a view to ensure the permanence and conclusion of studies of deaf academics entering Academic Education.